DETERMINATION OF DESIGN PARAMETERS OF ARTICULATED JIB SYSTEMS OF PORTAL CRANE - Suglobov, V. V.; Tkachuk, K. V. (Science and Transport Progress, 2017)
Purpose. The study involves: 1) formation of an array of geometry, weight and variable data for the automated synthesis of articulated jib systems; 2) development of methodology of calculation and determination of rational design parameters of the articulated jib systems, depending on the main technical parameters of the portal crane (maximum and minimum working radius, cargo lift height, tail radius value, carrying capacity of crane); 3) conducting of the study of the methodology adequacy on computer portal crane models. Methodology. To determine the kinematic characteristics of each link of the articulated jib system (boom, arm, jib tie, counterweight, load) we developed a dynamic and mathematical models that allow us to describe the movement of the articulated jib system when luffing. For the first time the technique of calculation and determination of rational design parameters of the articulated jib systems depending on the technical parameters of the portal crane. Findings. The conducted mathematical modeling allowed scientifically proving the usefulness of the proposed methodology for determining the design parameters of the articulated jib systems. The designed package of geometry, weight and variable data helps to simplify the process of preparatory calculations before the automated synthesis and to optimize the design of the articulated jib systems of portal cranes. Originality. For the first time the work proposes the technique for calculation of the parametric data that allow us to determine the rational design parameters of the articulated jib system. There are developed local programs for the integrated optimization synthesis that make it possible to select the best design option simultaneously by several quality criteria and functional constraints. Practical value. The proposed method of calculating the design parameters can be used in the design of new and modernization of existing portal cranes with the articulated jib systems, which, in turn, will reduce the material and energy consumption of the cranes.